Is Foreign Employment a Preferred Informed Choice among Households? Evidence from Nepal - Sharma, Bishnu Prasad (Economic Journal of Development Issues, 2019)
Foreign employment is one of the most significant phenomena impacting a wide range of dimensions in South Asian economies that characterize a large population out-migrating for work. whether sending a member for foreign employment a preferred informed choice of households in such economies, is not known. This paper aims to examine this research question using a binary logit model using indicators of household informed decision making, leadership qualities and the access to social networks. The findings indicated that foreign employment is not a preferred choice of households but is primarily the decision of the individual to go for foreign employment rather remain unemployed and economically insecure at home. Further analysis revealed that outstanding loans were higher, and the loans paid last year were also higher for foreign employment households compared to non-foreign employed households. The mean per capita consumption of households with foreign employed member were not statistically different than those of non-foreign employed households indicating no significant welfare gain for a majority of foreign employed labour households.